Produção de óxido nitroso de solo cultivado com feijoeiro comum irrigado em sistema plantio direto no cerrado - COSTA, Adriana Rodolfo da (2011)
The loss of nitrogen from the soil-plant system has economic and environmental repercussions, especially when nitrous oxide is emitted to the atmosphere. The aim of this study was to evaluate the emission of nitrous oxide (N2O) in the production system of irrigated commom beans under no-tillage, with brachiaria grass as cover plant (green manure), as affected by the application of different N sources. The experiment was conducted at Embrapa Rice and Beans, in a clayey Haplic Ferralsol. Six areas planted with common beans in no-till system, with sprinkler irrigation, center pivot, were evaluated in the fall/winter period of 2009. In each area (150 m2) a different source on N (treatments) was applied. The total area of the study was 1000 m2. The treatments were: no N (control), urea, ammonium sulfate (A.S.), urea + urease inhibitor (Ur.+Inhi.), urea combined with charcoal (Ur.+Car.), biological fixation nitrogen (B.F.N.), Cerrado (Cer). One hundred kg of N ha-1 was applied in all areas: 20% at sowing together with the seed at the same depth and 80% as top dressing, 25 days after planting. Periods, whose N2O fluxes were more important, were selected for more detailed study, including soil biological variables. The N2O concentration was determined by gas chromatography. Concurrently, soil moisture, temperature, water filled pore space (WFPS), pH and parameters related to the microbial biomass were also measured. The variables that influence soil N2O fluxes during the growing cycle of the bean are: the levels of nitrate in the soil, pH, moisture and WFPS, indicating conditions that favor the denitrification process. The highest emissions of N2O, occur in the following treatments: urea with urease inhibitor, biological nitrogen fixation and urea associated with charcoal, 70%, 36% and 32% higher then that observed in the control, respectively. The emission factors observed in this study are below the lowest levels suggested by IPCC (Intergovernmental Panel on Climate Change). After fertilization at sowing, the variables that control the emission of N2O are basal respiration, microbial biomass carbon (MBC), microbial biomass nitrogen (MBN), total organic carbon (TOC), soil moisture and WFPS. The charcoal combined with urea provides better conditions for microorganisms, increasing MBC and microbial quocient. After topdressing N2O fluxes are lower than at sowing, possibly due to higher N losses through volatilization or increased demand for N by the plant and consequent higher N uptake by plants. The ammonium sulfate source shows the highest N2O fluxes in this period. The variables that control N2O emission in this period are: MBN, pH, moisture and WFPS. During the senescence of the bean plants urea combined with urease inhibitor and biological fixation nitrogen are the treatments that most emitt N2O. The variables that controll the fluxes are soil temperature and TOC.